FREQUENCY OF BACTERIAL MICROORGANISMS IN EXUDATIVE PLEURAL EFFUSION - Ali, Akhtar; Ghuman, Faiza Dildar; Hasan, Syed Muhammad; Iqbal, Sadia; ., Ahsan; Adnan, Syed Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the bacterial etiology of exudative pleural effusion. Methodology: A cross-sectional study on newly diagnosed patients of Exudative Pleural Effusion was conducted at medicine department of Dow University Hospital, Karachi during the period of six months from August 2019 to February 2020. Out of 177 patients of age 18-75 years were enrolled by consecutive non-probability sampling technique. Patients of Tuberculosis, heart failure, chronic liver disease, chronic renal failure or patients on diuretic therapy were excluded. Pleural fluid was detected via chest x-ray followed by diagnostic thoracentesis for bacterial confirmation. Results: Out of 177 Exudative Pleural Effusion patients, male patients were 106 (59.9%) and female patients were 71 (40.1%). Bacterial microorganisms were detected in 67 (37.9%) patients, among which most common were Staphylococcus Aureus 13 (19.4%) and Escherichia Coli 13 (19.4%) followed by Acetobacter Baumannii 12 (17.9%), Streptococcus pneumonia 9 (13.4%), Staphylococcus Epidermidis 6 (9.0%), Pseudomonas Aeruginosa 5 (7.5%), Enterococcus Spp 5 (7.5%) and Enterobacter Aerogenes 4 (6.0%). Conclusion: Frequency of bacterial microorganisms in Exudative Pleural Effusion was high among adult patients. Escherichia Coli, Staphylococcus Aureus and Acetobacter Baumannii were commonly detected pathogens from Exudative Pleural Effusion. Keywords: Pleural Effusion, Diagnostic, Morbidity, Mortality, Therapeutic.